Perancangan dan Pengembangan Websıte Company Profıle PT Batam Trans - Tony Wibowo; Ricky Verniando (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
PT Batam Trans is a company that was established in 2010 which engaged in the field of expedition trucks. The obstacle faced by PT Batam Trans during its business activities is that there is no web-based information system as a promotional medium in the world of information technology. The service uses applied research solutions with the aim of solving the obstacles faced by PT Batam Trans in this digital world. Therefore, a Company Profile Website was created which aims to help PT Batam Trans companies in promoting their company. By applying this company profile website results, it is hoped that it can help PT Batam Trans companies in promoting their company.